2004
DOI: 10.1242/jeb.00854
|View full text |Cite
|
Sign up to set email alerts
|

Response latencies to postural disturbances in three species of teleostean fishes

Abstract: Flow in aquatic systems is characterized by unsteadiness that creates destabilizing perturbations. Appropriate correction responses depend on response latency. The time between a disturbance induced by either removal of a flow refuge or striking various parts of the body with a narrow water jet was measured for three species, chosen as examples of modes in teleostean body/fin organization that are expected to affect stability. Creek chub Semotilus atromaculatus is representative of fusiform-bodied soft-rayed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 57 publications
3
44
0
1
Order By: Relevance
“…The angular momentum transferred to the fish from the eddy is therefore assumed to have resulted in a body rotation that was not countered by the fish until after a body rotation of 45deg occurred. Webb (Webb, 2004a) showed that the yawing and pitching response latency of creek chub is 123±19ms, which coincides well with our observation that active deployment of fins occurred approximately five video images (133ms) after initiation of body rotation. In all of the spills analyzed, fin deployment was not initiated until after a 45deg body rotation occurred.…”
Section: Discussionsupporting
confidence: 88%
“…The angular momentum transferred to the fish from the eddy is therefore assumed to have resulted in a body rotation that was not countered by the fish until after a body rotation of 45deg occurred. Webb (Webb, 2004a) showed that the yawing and pitching response latency of creek chub is 123±19ms, which coincides well with our observation that active deployment of fins occurred approximately five video images (133ms) after initiation of body rotation. In all of the spills analyzed, fin deployment was not initiated until after a 45deg body rotation occurred.…”
Section: Discussionsupporting
confidence: 88%
“…For example, entraining and bow waking fish only exhibit intermediate M O2 values at the lowest flow, suggesting that stability costs may be higher at low flow. As velocity increases, fluid interactions with body and fin posture can generate trimming forces to increase thrust passively and lower stability costs (Webb, 2002;Webb, 2004). In addition, lower M O2 values for entraining and bow waking arise from the transition from branchial pumping to ram ventilation, which has been shown to decrease oxygen consumption by 10% in rainbow trout (Steffensen, 1985).…”
Section: Oxygen Consumption Of Trout Around a Cylindermentioning
confidence: 99%
“…Rotational disturbances present large control problems for swimming fish (Eidietis et al, 2002;Webb, 2002;Webb, 2004). In addition, rotational perturbations are more likely to be amplified than translational perturbations (Hoerner, 1975).…”
Section: Pelvic Fin Functional Significancementioning
confidence: 99%